(untitled) (Isagoge - Journal of Humanities and Social Sciences, 2022)
The article analyzes the importance of love for the construction of human identity from childhood, which is the foundation of all life. The construction of identity takes place through self-knowledge and recognition of other human beings as their peers. Affection and love as foundations of childhood are instruments for achieving an egalitarian and just society. The essence of human beings and the formation of their identity will be analyzed based on lived experiences and the need for love in the construction or reconstruction of the individual. A human being inserted in an environment divergent from the established social and legal rules will only have their identity adapted to society if empathy comes from the members of this society. Love is an essential feeling and commandment for the construction or reconstruction of human identity.